Multiple intrathoracic thrombosis detected on ct scan in patient with antiphospholipid antibody syndrome: case report - Safarini, Bekti; Intisari, Dewi (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2023)
Antiphospholipid antibody syndrome (APS) is the clinical correlation between antiphospholipid antibodies and hypercoagulability syndrome. The prevalence of APS in the general population is undetermined. APS disease carries a notable risk of vascular thrombosis. CT scan is the preferred imaging method for assessing thrombosis, although the timing of image acquisition should be considered. The case report detailed the discovery of many intrathoracic thromboses on a CT scan of a patient diagnosed with the uncommon condition APS. Case study: A 34-year-old woman was hospitalized due to dyspnea, cough, and a 3 kg weight loss over a three-month period. She has a background in Deep Vein Thrombosis (DVT). The test results showed abnormalities in protein C, protein S, and high D-dimer levels. The CT scan revealed numerous intrathoracic thrombi. Antiphospholipid syndrome (APS) is an immunological condition that elevates the likelihood of blood clot formation, resulting in thrombosis inside the arteries and veins. The approximate occurrence rate of APS is five occurrences per 100,000 individuals annually. Antiphospholipid syndrome (APS) leads to the formation of blood clots in the legs, a condition referred to as deep vein thrombosis (DVT). This patient had a history of deep vein thrombosis (DVT) and many blood clots within the chest cavity. A CT scan revealed persistent blood clots in the main pulmonary artery and the right and left pulmonary arteries. Antiphospholipid syndrome (APS) can lead to the formation of blood clots in both arteries and veins. CT scan is the preferred method for evaluating thrombosis, and numerous phases are required to examine all blood arteries.